PECULIARITIES OF APPLICATION OF COMPULSORY MEDICAL MEASURES TO MENTALLY ILL PERSONS WHO HAVE COMMITTED A CRIMINAL OFFENCE IN THE USA - Holdberh, Natalya; Bila, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: to analyse the legislation of the United States of America (hereinafter - the USA) regulating the application of compulsory medical measures to mentally ill persons who have committed a criminal offence. Research methods: analysis and synthesis, cognitive and analytical, methods of systematisation and generalisation. Results: the analysis of the criminal and procedural legislation of the United States made it possible to assert that the concept of insanity and sanity for persons with mental disorders is a set of criteria (mental and legal) that undoubtedly require further study, clarification and improvement from the point of view of medicine, theory of criminal and procedural law, forensic practice. Discussion: components of a comprehensive approach to the application of compulsory medical measures to mentally ill persons in the United States.